2005
DOI: 10.1111/j.1742-4658.2005.04624.x
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan‐4 is a signaling molecule for stromal cell‐derived factor‐1 (SDF‐1)/ CXCL12

Abstract: Stromal cell‐derived factor‐1 (SDF‐1)/CXCL12, the ligand for CXCR4, induces signal transduction. We previously showed that CXCL12 binds to high‐ and low‐affinity sites expressed by primary cells and cell lines, and forms complexes with CXCR4 as expected and also with a proteoglycan, syndecan‐4, but does not form complexes with syndecan‐1, syndecan‐2, CD44 or beta‐glycan. We also demonstrated the occurrence of a CXCL12‐independent heteromeric complex between CXCR4 and syndecan‐4. However, our data ruled out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 41 publications
6
59
0
Order By: Relevance
“…40 In this study, we also found that expression of Syn4 on VPCs was upregulated soon after vascular injury and then returned to the control level ( Figure 6D). It is attempting to speculate that the shedding of upregulated Syn4 from BM cells contributes to the mobilization of VPCs and subsequent neointimal formation.…”
Section: Circulating Vpcs In Syn4supporting
confidence: 69%
See 1 more Smart Citation
“…40 In this study, we also found that expression of Syn4 on VPCs was upregulated soon after vascular injury and then returned to the control level ( Figure 6D). It is attempting to speculate that the shedding of upregulated Syn4 from BM cells contributes to the mobilization of VPCs and subsequent neointimal formation.…”
Section: Circulating Vpcs In Syn4supporting
confidence: 69%
“…It should be noted that both stromal cell-derived factor-1 and its receptor CXCR4 play a crucial role in the mobilization and homing of BM-VPCs after vascular injury 28,39 and that Syn4 is a signaling molecule for the stromal cell-derived factor-1/ CXCR4 pathway. 40 In this study, we also found that expression of Syn4 on VPCs was upregulated soon after vascular injury and then returned to the control level ( Figure 6D). It is attempting to speculate that the shedding of upregulated Syn4 from BM cells contributes to the mobilization of VPCs and subsequent neointimal formation.…”
supporting
confidence: 69%
“…Recent studies showed that several other factors such as syndecan and IFN-␥, influence the SDF-1/CXCR4 signaling system. 16,43 Essential physiological and pathological roles of SDF-1/CXCR4 interactions have been increasingly demonstrated in various tissues and culture systems. 11,16 -19,43 SDF-1 is broadly and constitutively expressed in stromal cells and endothelial cells in numerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Our previous study showed that heparan sulfate proteoglycan was abundant in fibrous stroma of ICC, whereas heparan sulfate proteoglycan expression was negligible in the surrounding liver. 54 Furthermore, Charnaux and colleagues 43 reported that a proteoglycan, syndecan-4, behaves as a SDF-1 receptor, and is selectively involved in signal transduction induced by SDF-1. Taken together, it seems possible that the specific interactions of SDF-1 and TNF-␣ with their receptors expressed on ICC cells are likely to occur in such tumor-stromal microenvironments, and that these interactions are responsible for the characteristic biological behaviors of ICC such as invasion and migration.…”
Section: Cxcr4 and Cholangiocarcinoma 1165mentioning
confidence: 99%
“…Syndecan-4 (Syn4) is a heparan sulphate PG reported to modulate FGF signalling in vitro (Iwabuchi and Goetinck, 2006;Tkachenko et al, 2004;Tkachenko and Simons, 2002). In addition, Syn4 interacts with chemokines (Brule et al, 2006;Charnaux et al, 2005) and with the planar cell polarity (PCP) pathway (Matthews et al, 2008;Muñoz et al, 2006). As Syn4 also interacts with fibronectin and integrins and is required for the formation of focal adhesions (Woods and Couchman, 2001), its main role has been thought to be in cell migration.…”
Section: Introductionmentioning
confidence: 99%